Research on Recidivism of Burglary Crimes and the Path of Governance: An Empirical Study of 795 Burglary Convictions in City C - Zhang, Wenhua (International Journal of Global Economics and Management, 2024)
As a long-standing type of crime, theft has become a focus of attention in both academia and judicial practice due to its high recidivism rate. To gain a deeper understanding of this phenomenon, this study takes 795 theft verdicts from C city over the past 8 years as a sample to investigate the characteristics, causes, and effective governance strategies of recidivism in theft. At the same time, it analyzes in depth the social structure, judicial and legal practices that contribute to the sustained increase in recidivism rates. In response to the above issues, measures have been proposed to optimize the trial procedures, establish a "replacement punishment" system, and improve the application of probation in theft crimes. The aim is to provide practical and feasible solutions for the problem of repeated theft in C city and even wider areas, and to provide policy references and theoretical support for preventing and reducing the recurrence of theft crimes.